The Paradox Of Perpetuity: When Wakaf Khas (Specific Waqf) Becomes Frozen Assets In Malaysia: A Critical Analysis - Mohammad Hidir Baharudin; Umbas Krisnanto; Jasman Jasman; Rahmawati Mohd Yusoff (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2026)
The institution of waqf (Islamic endowment) is a cornerstone of Islamic social finance, intended to provide perpetual socioeconomic benefits to the Muslim community. However, in Malaysia, an estimated 87% of the 30,000 hectares of waqf land remains underdeveloped, resulting in billions of ringgits in “frozen” assets. A significant yet underexplored contributor to this phenomenon is the overproliferation of wakaf khas (specific waqf), in which donors strictly limit the use of their endowments to highly specific purposes that may become obsolete, unviable, or redundant over time. This article provides a comprehensive and analytical examination of the wakaf khas dilemma in Malaysia. It critically analyses the Islamic jurisprudential maxim “the condition of the waqif is like the text of the Lawgiver” (شَرْطُ الوَاقِفِ كَنَصِّ الشَّارِعِ) against the higher objectives of Shariah (maqasid al-shariah) and the principle of public interest (maslahah). The article evaluates the legislative frameworks across all 14 Malaysian states, focusing on the provisions for istibdal (substitution) as a remedy for frozen assets. By integrating contemporary fatwas and assessing the governance structures of State Islamic Religious Councils (SIRCs), this paper argues for a paradigm shift from rigid legal formalism to a welfare-oriented, maqasid-driven approach to unlock the economic potential of wakaf khas in Malaysia. The study employs a qualitative doctrinal legal methodology, combining content analysis of primary Islamic legal texts (turath), statutory instruments, and fatwa resolutions with critical comparative analysis across the four Sunni schools of thought and beyond.